Rapid Generation of In-House Serological Assays Is Comparable to Commercial Kits Critical for Early Response to Pandemics: A Case With SARS-CoV-2 - Auerswald, Heidi; Eng, Chanreaksmey; Lay, Sokchea; In, Saraden; Eng, Sokchea; Vo, Hoa Thi My; Sith, Charya; Cheng, Sokleaph; Delvallez, Gauthier; Mich, Vann; Meng, Ngy; Sovann, Ly; et al. (Frontiers in Medicine, 2022)
Introduction: Accurate and sensitive measurement of antibodies is critical to assess the prevalence of infection, especially asymptomatic infection, and to analyze the immune response to vaccination during outbreaks and pandemics. A broad variety of commercial and in-house serological assays are available to cater to different laboratory requirements; however direct comparison is necessary to understand utility. Materials and Methods: We investigate the performance of six serological methods against SARS-CoV-2 to determine the antibody profile of 250 serum samples, including 234 RT-PCR-confirmed SARS-CoV-2 cases, the majority with asymptomatic presentation (87.2%) at 1-51 days post laboratory diagnosis. First, we compare to the performance of two in-house antibody assays: (i) an in-house IgG ELISA, utilizing UV inactivated virus, and (ii) a live-virus neutralization assay (PRNT) using the same Cambodian isolate as the ELISA. In-house assays are then compared to standardized commercial anti-SARS-CoV-2 electrochemiluminescence immunoassays (Elecsys ECLIAs, Roche Diagnostics; targeting anti-N and anti-S antibodies) along with a flow cytometry based assay (FACS) that measures IgM and IgG against spike (S) protein and a multiplex microsphere-based immunoassay (MIA) determining the antibodies against various spike and nucleoprotein (N) antigens of SARS CoV-2 and other coronaviruses (SARS CoV 1, MERS CoV, hCoVs 229E, NL63, HKU1). Results: Overall, specificity of assays was 100%, except for the anti-S IgM flow cytometry based assay (96.2%), and the in-house IgG ELISA (94.2%). Sensitivity ranged from 97.3% for the anti-S ECLIA down to 76.3% for the anti-S IgG flow cytometry based assay. PRNT and in-house IgG ELISA performed similarly well when compared to the commercial ECLIA: sensitivity of ELISA and PRNT was 94.7% and 91.1%, respectively, compared to S- and N-targeting ECLIA with 97.3% and 96.8%, respectively. The MIA revealed cross-reactivity of antibodies from SARS-CoV-2-infected patients to the nucleocapsid of SARS-CoV-1, and the spike S1 domain of HKU1. Conclusion: In-house serological assays, especially ELISA and PRNT, perform similarly to commercial assays, a critical factor in pandemic response. Selection of suitable immunoassays should be made based on available resources and diagnostic needs.